Developing a neuro-linguistic (NLP) programming-based communication module for self-esteem enhancement: Cases of juvenile offenders in rehabilitation settings - Cik Ibrahim, Nur Sharina; Mokhter, Siti Hajar; Abdul Aziz , Nadiah (Journal of Islamic, Social, Economics and Development, 2025)
This study focuses on the development of a Neuro-Linguistic Programming (NLP)-based communication module designed to foster self-esteem among juvenile offenders in rehabilitation settings. The objective was twofold: to construct a structured NLP-based communication module and to evaluate its content validity and reliability. The module was developed following established module development frameworks by Jamaluddin and Russell, incorporating key components such as goals, theoretical foundations, rationale, target groups, identified needs, and learning objectives. Guided by Russell’s eight-step model, the design was integrated into qualitative methods. A pilot test involving a single juvenile subject was conducted, where the participant engaged in the full module and participated in follow-up interviews. Reliability was assessed using the cross-check and repeated interview techniques with interview questions aligned to module objectives. To determine content validity, expert review was employed through the external critic method, resulting in a high validity score of 93%. The findings indicated that the NLP-based communication module is valid and reliable, suggesting its potential as an effective rehabilitative communication tool for improving self-esteem among juvenile offenders.